2010
DOI: 10.1002/jmri.22353
|View full text |Cite
|
Sign up to set email alerts
|

In vivo MR imaging tracking of transplanted mesenchymal stem cells in a rabbit model of acute peripheral nerve traction injury

Abstract: Purpose: To investigate in vivo MRI tracking mesenchymal stem cells (MSCs) in peripheral nerve injures using a clinically available paramagnetic contrast agent (Gd-DTPA) and commercially available rhodamine-incorporated transfection reagents (PEI-FluoR). Materials and Methods:After bone marrow MSCs were labeled with Gd-DTPA and PEI-FluoR complex, the labeling efficacy and longevity of Gd-DTPA maintenance were measured and cell viability, proliferation, and apoptosis were assessed. Thirty-six rabbits with acute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 39 publications
0
16
1
Order By: Relevance
“…40,48 The proportion of cells that survived was reported to be up to 38%. 42 Furthermore, the transition from stem cell to Schwann cell has been encountered previously and thus indicates that this could be a vital factor in explaining the beneficial effect. 6,7,39,45 Schwann cells, however, not only myelinate; Höke et al 14 showed that the Schwann cell phenotype can be modulated, for example, into motor or sensory Schwann cells.…”
mentioning
confidence: 85%
“…40,48 The proportion of cells that survived was reported to be up to 38%. 42 Furthermore, the transition from stem cell to Schwann cell has been encountered previously and thus indicates that this could be a vital factor in explaining the beneficial effect. 6,7,39,45 Schwann cells, however, not only myelinate; Höke et al 14 showed that the Schwann cell phenotype can be modulated, for example, into motor or sensory Schwann cells.…”
mentioning
confidence: 85%
“…MSCs were harvested and expanded as previously described ( 17 ). The tissue-engineered constructs were prepared according to the previously reported method ( 5 ).…”
Section: Tissue-engineered Constructsmentioning
confidence: 99%
“…The most acceptable explanation is that MSCs differentiate into Schwann-like cells to produce large amounts of various cytokines and growth factors that may promote neural cell survival and neuritogenesis, or take part in myelin formation directly [7,16,20,22,26]. Because implanted MSCs generate neural phenotypes specific to the lesion site [4,17,18,23,24], another transdifferentiation mechanism of MSCs is believed to be due to spontaneous fusion of MSCs with host cells rather than actual transdifferentiation [27].…”
Section: Introductionmentioning
confidence: 97%